Telemedicine for management of inflammatory bowel disease (myIBDcoach): a pragmatic, multicentre, randomised controlled trial. Issue 10098 (2nd September 2017) - de Jong, Marin J; van der Meulen-de Jong, Andrea E; Romberg-Camps, Mariëlle J; Becx, Marco C; Maljaars, Jeroen P; Cilissen, Mia; van Bodegraven, Ad A; Mahmmod, Nofel; Markus, Tineke; Hameeteman, Wim M; Dijkstra, Gerard; Masclee, Ad A; et al.
Summary: Background: Tight and personalised control of inflammatory bowel disease in a traditional setting is challenging because of the disease complexity, high pressure on outpatient clinics, and rising incidence. We compared the effects of self-management with a telemedicine system, which was developed for all subtypes of inflammatory bowel disease, on health-care utilisation and patient-reported quality of care versus standard care. Methods: We did this pragmatic, randomised trial in two academic and two non-academic hospitals in the Netherlands. Outpatients aged 18–75 years with inflammatory bowel disease and without an ileoanal or ileorectal pouch anastomosis, who had internet access and Dutch proficiency, were randomly assigned (1:1) to care via a telemedicine system (myIBDcoach) that monitors and registers disease activity or standard care and followed up for 12 months. Randomisation was done with a computer-generated sequence and used the minimisation method. Participants, health-care providers, and staff who assessed outcome measures were not masked to treatment allocation. Primary outcomes were the number of outpatient visits and patient-reported quality of care (assessed by visual analogue scale score 0–10). Safety endpoints were the numbers of flares, corticosteroid courses, hospital admissions, emergency visits, and surgeries. Analyses were by intention to treat. This trial is registered withClinicalTrials.gov, numberNCT02173002 . Findings: Between Sept 9, 2014, and May 18, 2015, 909 patients were randomly assigned to telemedicine (n=465) or standard care (n=444). At 12 months, the mean number of outpatient visits to the gastroenterologist or nurse was significantly lower in the telemedicine group (1·55 [SD 1·50]) than in the standard care group (2·34 [1·64]; difference −0·79 [95% CI −0·98 to −0·59]; p<0·0001), as was the mean number of hospital admissions (0·05 [0·28] vs 0·10 [0·43]; difference −0·05 [–0·10 to 0·00]; p=0·046). At 12 months, both groups reported high mean patient-reported quality of care scores (8·16 [1·37] in the telemedicine group vs 8·27 [1·28] in the standard care group; difference 0·10 [–0·13 to 0·32]; p=0·411). The mean numbers of flares, corticosteroid courses, emergency visits, and surgeries did not differ between groups. Interpretation: Telemedicine was safe and reduced outpatient visits and hospital admissions compared with standard care. This self-management tool might be useful for reorganising care of inflammatory bowel disease towards personalised and value-based health care. Funding: Maastricht University Medical Centre and Ferring.